1. x^2 + x = 0
D = 1 - 4 * 1 * 0 = 1 - 0 = 1
2. 2x^2 + 5x = 0
D = 25 - 4 * 2 * 0 = 25
3. x^2 - 10x + 25 = 0
D = 100 - 4 * 1 * 25 = 0
4. 4x^2 - 12x + 9 = 0
D = 144 - 4 * 4 * 9 = 0
5. x^2 + 2x - 3 = 0
D = 4 - 4 * 1 * ( - 3 ) = 16 = 4^2
6. x^2 - 5x + 4 = 0
D = 25 - 4 * 1 * 4 = 9 = 3^2
7. 2x^2 - 2x - 4 = 0
x^2 - x - 2 = 0
D = 1 - 4 * 1 * ( - 2 ) = 9 = 3^2
8. x^2 = 2x + 3
x^2 - 2x - 3 = 0
D = 4 - 4 * 1 * ( - 3 ) = 16 = 4^2
9. x^2 = 10 - 3x
x^2 + 3x - 10 = 0
D = 9 - 4 * 1 * ( - 10 ) = 49 = 7^2
10. 4x + 21 = x^2
x^2 - 4x - 21 = 0
D = 16 - 4 * 1 * ( - 21 ) = 100 = 10^2
11. 6x + 7 = x^2
x^2 - 6x - 7 = 0
D = 36 - 4 * 1 * ( - 7 ) = 64 = 8^2
12.
3x^2 - 12 = 0; + [ x ≠ 0; x ≠ -3]
D = 0 - 4 * 3 * ( - 12 ) = 0 + 144 = 144 = 12^2
Объяснение: